Pigmentation phototype and prostate and breast cancer in a select Spanish population-A Mendelian randomization analysis in the MCC-Spain study. - Inés Gómez-Acebo; Trinidad Dierssen-Sotos; Camilo Palazuelos; Pablo Fernández-Navarro; Gemma Castaño-Vinyals; Jéssica Alonso-Molero; Carmen Urtiaga; Tania Fernández-Villa; Eva Ardanaz; Manuel Rivas-Del-Fresno; Ana Molina-Barceló; José-Juan Jiménez-Moleón; et al. (PLoS ONE, 2018)
INTRODUCTION:Phototype has been associated with an increased risk of prostate cancer, and it is yet unknown if it is related to other hormone-dependent cancers, such as breast cancer or whether this association could be considered causal. METHODS:We examined the association between the phototype and breast and prostate cancers using a Mendelian randomization analysis. We studied 1,738 incident cases of breast cancer and another 817 cases of prostate cancer. To perform a Mendelian randomization analysis on the phototype-cancer relationship, a genetic pigmentation score was required that met the following criteria: (1) the genetic pigmentation score was associated with phototype in controls; (2) the genetic pigmentation score was not associated with confounders in the relationship between phototype and cancer, and (3) the genetic pigmentation score was associated with cancer only through its association with phototype. Once this genetic score is available, the association between genetic pigmentation score and cancer can be identified as the association between phototype and cancer. RESULTS:The association between the genetic pigmentation score and phototype in controls showed that a higher genetic pigmentation score was associated with fair skin, blond hair, blue eyes and the presence of freckles. Applying the Mendelian randomization analysis, we verified that there was no association between the genetic pigmentation score and cancers of the breast and prostate. CONCLUSIONS:Phototype is not associated with breast or prostate cancer.